A Unravelling the Mechanisms of Exercise Induced Ischaemia, its Optimal Assessment, and Alleviation with Nitroglycerine. (31st May 2014) - Asrress, Kaleab N; Williams, Rupert; Chiribiri, Amedeo; Lockie, Timothy; Zeeshan Khawaja, M; Guilcher, Antoine; Sammut, Eva; Wesolowski, Roman; De Silva, Kalpa; Lumley, Matthew; Ihsan, Sana; Patterson, Tiffany; et al.
Abstract : Introduction: The mechanisms governing exercise-induced angina, its alleviation by the most common anti-anginal drug, nitroglycerine (GTN), and the best techniques to elucidate whether a stenosis causes sufficient ischaemia to warrant revascularisation are incompletely understood. In this multifaceted investigation we aimed to investigate these processes. Methods: A porcine model of coronary stenosis was developed for invasive assessment of coronary haemodynamics and perfusion MRI. Coronary lesions were created using an external balloon constrictor to investigate the optimal method of assessing stenosis severity, using an invasive standard for coronary ischaemia of Hyperemic Stenosis Resistance (HSR) and a non-invasive standard of adenosine stress perfusion cardiac MRI. In the human translation, 21 Patients with exertional angina and documented coronary artery disease underwent cardiac catheterisation via radial access and performed incremental exercise using a supine cycle ergometer. As they developed limiting angina, sublingual GTN was administered and exercise continued for two minutes at the same workload. Throughout exercise, distal coronary pressure and flow velocity, and central aortic pressure were recorded using sensor wires. After a period of rest, intravenous adenosine was administered to assess lesion severity using conventional catheter methods. Results: 64 lesions of varying severity were created in the porcine model showing that Fractional Flow Reserve (FFR) provided the best test of stenosis severity, which was significantly better than instantaneous wave-free ratio (iFR), Basal Stenosis Resistance (BSR), and resting Pd/Pa ratio. In the human translation, indices measured at peak exercise (HSR, FFR) performed significantly better than adenosine-based indices, which were superior to measurements at rest. Compared to peak exercise, patients continued to exercise post-GTN administration with less ischemia (P = 0.003). Coronary pressure and flow were maintained (P=NS), in the face of significant reduction in left ventricular afterload (0.01). On wave intensity analysis, significant increases were seen in both the energy of the diastolic microcirculatory backward expansion wave, and the systolic backward compression wave related to myocardial contractility (0.05). Conclusions: Coronary ischaemia can be studied using a porcine model in the catheter laboratory as well as MRI environment. This model showed that the adenosine based indices, HSR and FFR, performed significantly better than those measured at rest, suggesting that these should be used in the assessment of lesion severity. The human exercise protocol provides a new paradigm with which the physiology of ischemia as well as the performance of novel and established anti-anginals can be studied. Administration of GTN causes harmonious changes in the systemic and coronary circulation that combine to reduce afterload while maintaining coronary perfusion. The study also demonstrates, for the first time, a coronary derived index with potential to measure myocardial contractility.